1‐Chloronaphthalene‐Induced Donor/Acceptor Vertical Distribution and Carrier Dynamics Changes in Nonfullerene Organic Solar Cells and the Governed Mechanism. Issue 3 (22nd January 2022) - He, Xinjun; Chan, Christopher C. S.; Kim, Jinwook; Liu, Heng; Su, Chun‐Jen; Jeng, U‐Ser; Su, Haibin; Lu, Xinhui; Wong, Kam Sing; Choy, Wallace C. H.
Abstract: Electron donors and acceptors in organic solar cells (OSCs) shall strike a favorable vertical phase separation that acceptors and donors have sufficient contact and gradient accumulation near the cathodes and anodes, respectively. Random mixing of donors/acceptors at surface will result in charge accumulation and severe recombination for low carrier‐mobility organic materials. However, it is challenging to tune the vertical distribution in bulk‐heterojunction films as they are usually made from a well‐mixed donor/acceptor solution. Here, for the first time, it presents with solid evidence that the commonly used 1‐chloronaphthalene (CN) additive can tune the donor/acceptor vertical distribution and establish the mechanism. Different from the previous understanding that ascribed the efficiency enhancement brought by CN to the improved molecular stacking/crystallization, it is revealed that the induced vertical distribution is the dominant factor leading to the significantly increased performance. Importantly, the vertical distribution tunability is effective in various hot nonfullerene OSC systems and creates more channels for the collection of dissociated carriers at corresponding organic/electrode interfaces, which contributes the high efficiency of 18.29%. This study of the material vertical distribution and its correlation with molecular stacking offers methods for additives selection and provides insights for the understanding and construction of high‐performance OSCs. Abstract : 1‐Chloronaphalene (CN) has been extensively employed as an additive to improve the donor/acceptor crystallization/phase segregation in organic solar cells. However, this work further uncovers that CN can tune the donor/acceptor vertical distribution in the blend film, which is revealed to be the dominant factor leading to the significantly improved efficiency and finally contributes to a best efficiency of 18.29%.